Mediação aplicada nas relações de consumo: dos direitos fundamentais à parceria público-comunitária para efetivar políticas públicas - Scortegagna, Franco (2021)
This Dissertation is part of the Constitutional Jurisdiction and Democracy Research Line. The scientific objective of this study was to verify the challenges for resolving conflicts in consumer relations in the extrajudicial sphere, public/community partnership in mediation. The first chapter analyzed the challenges of ensuring consumer rights, showing that new technologies, in addition to social interactions, helped society to adopt a culture directed towards consumerism. The phenomenon brought significant changes in the economic, political and social scenario, which have not yet can be measured. The citizen-consumer today has access to a diversity of choices, giving him the power to carry out operations and interact with any individual, anywhere in the world, wherever technology reaches. Chapter 2 dealt with the implementation of public policies and consumer rights in the face of growing economic integration, globalization, and showed that patterns of consumption production and acquisition of material goods have changed worldwide. Chapter 3 addressed the resolution of extrajudicial conflicts in public/community partnerships in mediation. The debate on consumer protection stands out, based on globalization, to harmonize market interests with human rights in post-modern times, of individualism and increasingly developed economic integration. Conflicts in consumer relations increasingly require actions and procedures aimed at protecting consumers. The objective is to balance the difficulties of access to Justice, through alternative methods, processes that allow, depending on their peculiarities, disputes to be resolved before the judicial phase. It was concluded that the initiative of the National Council of Justice, when editing Resolution 125/2010, the changes to the 2015 Civil Procedure Code, the regulation of mediation with its own law and, in its erga omnes view, the Consumer Protection Code , are regulations aligned with 21st century consumer protection issues. In this sense, the Consumer Counter, a project of the Faculty of Law of the University of Passo Fundo, is evidenced by the implementation of public/community partnership in mediation, when resolving citizen-consumer conflicts in the extrajudicial sphere, as well as by the awareness that the greatest The challenge that involves implementing public policies continues to be transforming the consumer into a citizen due to capitalism.